How Remote Work Can Foster a More Inclusive Environment for Transgender Developers - Ford Robinson, Denae; Milewicz, Reed; Serebrenik, Alexander (In proceedings of the ACM/IEEE ICSE 2nd International Workshop on Gender Equality in Software Engineering (GE), 2019)
In this position paper, we claim that remote work offers a mechanism of control for identity disclosure and empowerment of software developers from marginalized communities. By talking to several transgender software developers we identified three themes that resonate across the trans experience and intersect with the advantages to working in software development remotely: identity disclosure, high-impact technical work and the autonomy to disengage and re-engage. Based on these themes we identify several open questions that the research community should address.